IMPLEMENTASI KEBIJAKAN E-PARKING DI KOTA MEDAN PERIODE 2021-2024 - Sarumaha, Zeni Oktavianis; Hutahaean, Marlan; Tobing, Artha L. (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
The Medan City Government has implemented the E-Parking policy since 2021 as a solution to create a more transparent, modern parking system, and reduce leakage of Regional Original Income (PAD). This policy requires parking payments to be made non-cash through Electronic Data Capture (EDC) machines or digital applications. However, in its implementation in Kesawan Village, West Medan District, this policy still faces various obstacles that hinder its effectiveness. This study aims to analyze the implementation of the E-Parking policy for the 2021-2024 period, identify inhibiting factors, and evaluate its effectiveness using George C. Edward III's policy implementation theory, which includes communication, resources, disposition, and bureaucratic structure. The research method used is a qualitative approach with data collection techniques through interviews and documentation. This study shows that the implementation of E-Parking has not been optimal due to various challenges, such as lack of supervision and enforcement of regulations, misuse of the system by unscrupulous parking attendants, rejection from the community, and lack of socialization and training. As a result, this policy does not achieve its main objective of reducing illegal levies and increasing transparency in parking management. Based on various obstacles that occurred in the field, the Medan City Government finally stopped the E-Parking policy on July 1, 2024 and replaced it with a subscription parking system. In conclusion, efforts to improve supervision, wider socialization, and intensive training for each parking attendant are needed to ensure that future parking policies are more effective and acceptable to the public.